2020
DOI: 10.1021/jacs.0c09000
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Photoinduced Charge Transport Mechanism in 2D Conductive Metal Organic Frameworks

Abstract: Conductive metal organic frameworks (MOFs) represent a promising class of porous crystalline materials that have demonstrated potential in photo-electronics and photocatalytic applications. However, the lack of fundamental understanding on charge transport (CT) mechanism as well as the correlation of CT mechanism with their structure hampered their further development. Herein, we report the direct evidence of CT mechanism in 2D Cu-THQ MOFs and the correlation of temporal and spatial behaviors of charge carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 57 publications
4
75
0
Order By: Relevance
“…Moreover, the metallo-sp 2 c-COF-15 increases the mobility by 80 % compared to sp 2 c-COF-14 (Figure 6c), which might be associated with the formation of more efficient transport pathways by integrating the Cu II complex acceptor. [17] These results demonstrated that not only the band gap but also the carrier transport properties can be elaborated by the rational design of 2D sp 2 carbon frameworks. To further check the semiconducting properties of the as-synthesized sp 2 c-COFs, their conductivities were measured under vacuum and summarized in Figure S15.…”
Section: Charge Carrier Transportmentioning
confidence: 83%
“…Moreover, the metallo-sp 2 c-COF-15 increases the mobility by 80 % compared to sp 2 c-COF-14 (Figure 6c), which might be associated with the formation of more efficient transport pathways by integrating the Cu II complex acceptor. [17] These results demonstrated that not only the band gap but also the carrier transport properties can be elaborated by the rational design of 2D sp 2 carbon frameworks. To further check the semiconducting properties of the as-synthesized sp 2 c-COFs, their conductivities were measured under vacuum and summarized in Figure S15.…”
Section: Charge Carrier Transportmentioning
confidence: 83%
“…19 Several strategies have been developed to improve the charge separation efficiency of COFs, for example incorporating donor-acceptor (D-A) moieties 20,21 or halogen atoms in COFs, 22,23 constructing novel πconjugated building blocks, 24 and generating junctions with other semiconductors. 25 In addition to the above strategies, reducing the particle size of COFs to nanometer scale is a more facile method to improve the charge separation efficiency due to the possibility of charge carrier recombination is reduced in the short diffusion distance 26 . Therefore, the single-layer COFs (SLCOFs) offering the minimum diffusion distance for charge carriers will be the perfect candidate for photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Time‐resolved terahertz (THz) spectroscopy is an optical characterization technique now routinely used in the spectral range between 0.5 and 3 THz to monitor microscopic interactions and resolve key signature resonances in diverse materials such as superconductors, [ 1–4 ] semiconductors, [ 5,6 ] topological insulators, [ 7–10 ] heavy fermions, [ 11–13 ] ferroelectrics, [ 14,15 ] antiferromagnets, [ 16 ] and metal‐organic compounds. [ 17,18 ] One configuration commonly used for these experiments relies on a near infrared (NIR) ultrafast source and a pair of second‐order nonlinear crystals to generate and detect phase‐locked THz transients. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%